PELATIHAN PACKAGING DAN SARANA PROMOSI MINYAK SEREH WANGI PRODUKSI KELOMPOK TANI “GEMA INDUSTRI” DESA OENENU KECAMATAN BIKOMI TENGAH KABUPATEN TTU - Satmalawati, Maria Magdalena Endah Mulat; Metboki, Bernadina; Fallo, Kristoforus (Universitas Mataram, 2025)
Citronella oil produced by the “Gema Industri” farmer group is the only processor of essential oils made from citronella plants (Cymbopogon nardus) in North Central Timor Regency (TTU). The location of this home industry is in Oenenu Village, Bikomi Tengah District and has been carried out since 2000 until now using very simple equipment. Citronella oil distillation activities are carried out twice a week including marketing activities. The demand for citronella oil, especially in TTU Regency, which is adjusted to the purchasing power of the community, is not limited to pure citronella oil, but other products such as mixing several ingredients for medicinal purposes according to local wisdom such as massage oil or for treating toddlers in the form of a mixture of coconut oil and citronella oil in a ratio of 5:1 and other herbal ingredients. The results from the sale of products created by the “Gema Mandiri” farmer group have allowed this farmer group to survive until now. Product marketing is still done manually and relies on acquaintances and regular customers and there have been no more modern marketing breakthroughs such as the use of promotional media and digital marketing. In addition, the packaging of citronella oil is still limited to one size variant (100 ml) and has not been well designed, namely made of transparent plastic that does not meet product safety requirements, on the other hand the labeling is still very simple and does not fully describe the benefits of the product. The purpose of PkM is to help the